PENGARUH PEMANFAATAN INTERACTIVE FLAT PANEL (IFP) TERHADAP MINAT BELAJAR SISWA DALAM MATA PELAJARAN INFORMATIKA DI SMA NEGERI 9 BONE - Arsih, Nur Fani; Andi Hajar; Syarifnur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to: (1) determine students' learning interest before the use of IFP; (2) determine students' learning interest after the use of IFP; and (3) determine the effect of IFP utilization on students' learning interest in the Informatics subject at SMA Negeri 9 Bone. This study employed a quantitative approach with a One Group Pre-test Post-test Design. The research population consisted of all Grade XI students of SMA Negeri 9 Bone in the academic year 2025/2026. A total of 26 students from class XI A were selected using total sampling. The instrument used was a learning interest questionnaire based on a Likert scale (1–4) encompassing four indicators: sense of enjoyment, attentiveness in learning, interest in subject matter, and active participation. Data were analyzed using the Shapiro-Wilk normality test, paired sample t-test, N-Gain analysis, and Cohen's d effect size. The results showed: (1) the mean pre-test score for students' learning interest was 64,65 (High category); (2) the mean post-test score increased to 83,92, with 84.6% of students reaching the Very High category; (3) the paired sample t-test yielded t-value = 47,9168 > t-table = 2,0595 with p-value = 0.000 < 0.05, thus H₁ was accepted. The mean N-Gain of 0,5457 (Moderate category) and Cohen's d value of 9,3973 (Large category) further confirmed that the utilization of Interactive Flat Panel (IFP) had a significant and practically large effect on improving students' learning interest in the Informatics subject at SMA Negeri 9 Bone.